Implementasi Research Based Learning (RBL) pada Mata Kuliah IPA Terpadu di Program Studi Pendidikan Fisika - Fanny Rahmatina Rahim (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
To help realize UNP's vision towards a research-based university, awareness of Educators is needed to be active in providing innovation in classroom learning such as transforming conventional learning into research-based learning. This aim of this study was to analyze the implementation of research-based learning in Integrated Science courses Class VII in an effort to improve the ability to think critically and creatively. The study used the Quasi Experimental Research method with the design of the Pretest-posttest Control Group Design. The study was conducted in two sample classes obtained from cluster random sampling techniques by providing research-based learning treatment to the experimental class and ordinary learning to the control class. The research data was pre-test and post-test instrument, student response questionnaire and observation sheet during the learning process. With the implementation of research-based learning, the ability to think critically and creatively students of Physics Education FMIPA UNP was expected to be able to increase.